Differences in procedural knowledge after a "spaced" and a "massed" version of an intensive course in emergency medicine, investigating a very short spacing interval. Issue 1 (December 2016) - Breckwoldt, Jan; Ludwig, Jan; Plener, Joachim; Schröder, Torsten; Gruber, Hans; Peters, Harm
Abstract Background Distributing a fixed amount of teaching hours over a longer time period (spaced approach) may result in better learning than delivering the same amount of teaching within a shorter time (massed approach). While a spaced approach may provide more opportunities to elaborate the learning content, a massed approach allows for more economical utilisation of teaching facilities and to optimise time resources of faculty. Favourable effects of spacing have been demonstrated for postgraduate surgery training and for spacing intervals of weeks to months. It is however unknown, whether a spacing effect can also be observed for shorter intervals and in undergraduate medical education. Therefore, we aimed to evaluate the effect of a short spacing intervention within an undergraduate intensive course in emergency medicine (EM) on students' procedural knowledge. Methods An EM intensive course of 26 teaching hours was delivered over either 4.5 days, or 3.0 days. After the course students' procedural knowledge was assessed by a specifically developed video-case based key-feature test (KF-test). Results Data sets of 156 students (81.7 %, 191 students eligible) were analysed, 54 from the spaced, and 102 from the massed version. In the KF-test students from the spaced version reached a mean of 14.8 (SD 2.0) out of 22 points, compared to 13.7 (SD 2.0) in the massed version (p =  .002). Effect size was moderate (Cohen's d: 0.558). Conclusion A significant spacing effect was observable even for a short spacing interval in undergraduate medical education. This effect was only moderate and may be weighed against planning needs of faculty and teaching resources.